Testing Ranking Statistics for Joint Gravitational Wave and Gamma-Ray Burst Searches - Piotrzkowski, Brandon (Proceedings of the Wisconsin Space Conference, 2022)
Joint searches looking for associations between gravitational waves and gamma-ray bursts use ranking statistics toseparate real from random coincidences. However, there is no clear choice of which ranking statistics are more useful.We perform a simulated joint search simulating gravitational waves from the LIGO-Virgo-KAGRA (LVK) collabo-ration and Fermi-GBM gamma-ray candidates from the third operating run of LVK. We find evidence that rankingstatistics that include more information on the significance of the individual candidates perform better, although morerealistic data is needed to confirm this.